2022
DOI: 10.1038/s41598-022-06466-3
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Individual differences and musical preference via music-induced movement

Abstract: Movement is a universal response to music, with dance often taking place in social settings. Although previous work has suggested that socially relevant information, such as personality and gender, are encoded in dance movement, the generalizability of previous work is limited. The current study aims to decode dancers’ gender, personality traits, and music preference from music-induced movements. We propose a method that predicts such individual difference from free dance movements, and demonstrate the robustn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…While these studies have identified significant relations between dancing motion and personality, the predictive power of the produced models and correlations is at best modest. However, a more recent study by Agrawal et al (2020) traded the interpretability of bodily features for greater prediction power. Instead of using bodily features extracted by manual selection (e.g., speed or acceleration of body parts, or the distance or angle between them) or by dimensionality reduction (e.g., vertical or lateral speed), they used the covariance among the speed of body parts.…”
mentioning
confidence: 99%
“…While these studies have identified significant relations between dancing motion and personality, the predictive power of the produced models and correlations is at best modest. However, a more recent study by Agrawal et al (2020) traded the interpretability of bodily features for greater prediction power. Instead of using bodily features extracted by manual selection (e.g., speed or acceleration of body parts, or the distance or angle between them) or by dimensionality reduction (e.g., vertical or lateral speed), they used the covariance among the speed of body parts.…”
mentioning
confidence: 99%